Real-time monitoring of alkali release during CO2 gasification of different types of biochar. (1st November 2022) - Ge, Yaxin; Ding, Saiman; Kong, Xiangrui; Kantarelis, Efthymios; Engvall, Klas; Pettersson, Jan B.C.
Highlights: Alkali release increases remarkably during the final stage of wood char gasification. Alkali release from straw char decays throughout the gasification process. Char gasification reactivity is linked with the alkali release behavior. The dynamic character of alkali contributes to the catalytic effect and the alkali release behavior. Abstract: Potassium and sodium compounds play both positive and negative roles during biomass gasification, but the detailed behavior of alkali metal compounds remain incompletely understood. In this study, alkali release during CO2 gasification of biochar is characterized online with a surface ionization method in combination with thermogravimetric analysis of the char samples undergoing gasification. For wood chars, the alkali release rate follows a slowly decreasing trend as the char conversion proceeds, but increases by up to two orders of magnitude when the conversion approaches completion. In contrast, the alkali release from straw char is 40–50 times higher than observed for wood char and decreases continuously during the whole gasification process. A high temperature and a high CO2 concentration enhance both alkali release and char reactivity. The char preparation method also influences the alkali release from pine char, while the char reactivity is less affected. Alkali release and char reactivity are linked, but other factors including mineral content, surface area and char structure may play important roles for the observed reactivity. The results provide a basis for understanding of alkali behavior during gasification and may help optimize catalytic effects and reduce detrimental issues in biomass gasification.